Metastatic Colorectal Cancer Patient With Microsatellite Stability and BRAFV600E Mutation Showed a Complete Metabolic Response to PD-1 Blockade and Bevacizumab: A Case Report - Fang, Chongkai; Lin, Jietao; Zhang, Tao; Luo, Jiajun; Nie, Duorui; Li, Meng; Hu, Xue; Zheng, Yating; Huang, Xuewu; Xiao, Zhiwei (Frontiers in Oncology, 2021)
Background: Metastatic colorectal cancers (mCRC) patients harboring microsatellite stability (MSS) and the BRAFV600E-mutation show poor prognosis and do no benefit from immunotherapy. The identification and optimization of combined treatment strategies to improve the efficacy of immunotherapy in MSS patients, who account for the majority of mCRC cases, is the current research hotspot. Case Summary: In this report, we discuss a case of a recurrent mCRC patient with positive programmed death ligand 1 (PD-L1) expression (30%), MSS, and BRAFV600E-mutation, who responded significantly to the combined treatment with nivolumab and bevacizumab, and exhibited a progression-free survival (PFS) of more than 17 months. Our findings indicate that combined anti-angiogenic therapy could improve the efficacy of immunotherapy and prolong the patient’s survival. Conclusion: This is the first MSS colorectal cancer case report to present a positive response to immunotherapy and bevacizumab.